Process Evaluation of a School-Based High-Intensity Interval Training Program for Older Adolescents: The Burn 2 Learn Cluster Randomised Controlled Trial - Sarah G. Kennedy; Angus A. Leahy; Jordan J. Smith; Narelle Eather; Charles H. Hillman; Philip J. Morgan; Ronald C. Plotnikoff; James Boyer; David R. Lubans (MDPI AG, 2020)
Process evaluations can help to optimise the implementation of school-based physical activity interventions. The purpose of this paper is to describe the process evaluation of a school-based high-intensity interval training (HIIT) program for older adolescent students, known as Burn 2 Learn (B2L). B2L was evaluated via a cluster randomised controlled trial in 20 secondary schools (10 intervention, 10 control) in New South Wales, Australia. Teachers (n = 22 (55% female)) from the 10 intervention schools, delivered the program over three phases (Phases 1 and 2, 6 months; Phase 3, 6 months) to older adolescent students (n = 337 (50% female); mean ± standard deviation (SD) age = 16.0 ± 0.4 years). Process evaluation data were collected across the 12-month study period. Teachers delivered 2.0 ± 0.8 and 1.7 ± 0.6 sessions/week in Phases 1 and 2 respectively (mean total 25.9 ± 5.2), but only 0.6 ± 0.7 sessions/week in Phase 3. Observational data showed that session quality was high, however heart rate (HR) data indicated that only half of the students reached the prescribed threshold of ≥85% predicted HRmax during sessions. Over 80% of teachers reported they intended to deliver the B2L program to future student cohorts. Almost 70% of students indicated they intended to participate in HIIT in the future. Teachers considered the program to be adaptable, and both students and teachers were satisfied with the intervention. B2L was implemented with moderate-to-high fidelity in Phases 1 and 2, but low in Phase 3. Our findings add to the relatively scant process evaluation literature focused on the delivery of school-based physical activity programs.